2003
DOI: 10.1161/01.hyp.0000053447.64213.c4
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Adrenomedullin System in the Transition From LVH to Heart Failure in Rats

Abstract: Abstract-We investigated whether adrenomedullin (AM) participates in the pathophysiology during the transition from left ventricular hypertrophy (LVH) to heart failure (HF). We used the Dahl salt-sensitive (DS) rat model, in which systemic hypertension causes LVH at the age of 11 weeks, followed by HF at the age of 18 weeks. Two molecular forms of AM levels in the plasma and myocardium at the LVH stage were significantly elevated compared with those in controls, and they were further increased at the HF stage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…3,[27][28][29] The mechanism by which AM exerts its effects on cardiomyocytes is not fully understood. A previous report showed that AM signaling depends on the combination of CRLR (calcitonin receptor-like receptor) and RAMP2 (receptor activity- modifying proteins), resulting in activation of the AM receptor.…”
Section: Discussionmentioning
confidence: 99%
“…3,[27][28][29] The mechanism by which AM exerts its effects on cardiomyocytes is not fully understood. A previous report showed that AM signaling depends on the combination of CRLR (calcitonin receptor-like receptor) and RAMP2 (receptor activity- modifying proteins), resulting in activation of the AM receptor.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 After 3 weeks of administration of fasudil, hemodynamic studies (direct measurement of BP and heart rate) were performed with the animals under anesthesia, as reported previously. 17 Blood was obtained from the carotid artery, and the plasma was stored at Ϫ80°C until assay.…”
Section: Hemodynamic Measurement and Blood Samplingmentioning
confidence: 99%
“…After cooling, the boiled medium was evaporated in a vacuum until dry. Immunoradiometric assay for rat AM-m and AM-total (AM-m+AM-Gly) was performed using a recently developed specific immunoradiometric assay kit (AM RIA SHIONOGI) with some modifications, as previously reported [21,25]. AM-Gly was calculated as following formula: (AM-Gly)=(AMtotal)À(AM-m).…”
Section: Measurement Of Am-m and Am-gly Levelsmentioning
confidence: 99%
“…Second, recent studies have revealed that two molecular forms of AM, an active mature form of AM (AM-m), and an intermediate inactive form of glycine-extended AM (AM-Gly), circulate in human plasma, AM-Gly being the dominant circulating form [19,20]. In addition, we have very recently shown that the major molecular form of AM in cardiac tissues is AM-m and that this form of AM is increased in left ventricular hypertrophy (LVH) and heart failure [21]. However, which molecular form of AM is predominantly secreted by cultured cardiac fibroblasts remains unknown.…”
Section: Introductionmentioning
confidence: 99%